Diagnostic utility and impact of ultrasonography by primary health care physician: an observational study - Qureshi, Uruj Altaf; Bashir, Khalid; Rasool, Mahbooba (International Journal Of Community Medicine And Public Health, 2019)
Background: Ultrasound appears to be a suitable diagnostic technology for use in primary care and community settings. It plays a pivotal role in evaluation of patients and helps in making timely diagnosis and more widely on referral pathways into secondary care. Methods: The study was conducted at the primary health centre Hazratbal, which is one of the primary health centre of field practice area of the Department of community medicine, Government Medical College, Srinagar. This observational study was conducted over a period of three months where 255 patients were scanned by a primary care physician (sonologist). For each patient scanned, the ultrasound performing physician completed a standardized data collection form including patient demographics, clinical details, indications for ultrasound and ultrasound findings. Results: A total of 255 patients were scanned during the study period. Males were 43 (17%) and females were 212 (83%). Maximum number of patients were in the age range of 25-34 years, n=96 (38%). Among the patients scanned 66 (24.44%) were obstetric cases. Acute diffuse abdominal pain n=32 (11.85%) was the most common clinical presentation followed by pain upper abdomen n=28 (10.37%) among non-obstetric patients. Ovarian cyst was the most common finding, followed by fatty liver and bilateral nephrolithiasis. Conclusions: The utility of ultrasonography in the hands of primary care physician is of great value. It is cost effective option, especially in this part of the world. We need to give expertise to primary care physicians in order to provide better health care at primary health care settings, which will lessen the burden of referrals.